2012
DOI: 10.1161/circresaha.112.274548
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosation of β-Catenin and p120 Catenin

Abstract: Rationale Endothelial adherens junction proteins constitute an important element in the control of microvascular permeability. Platelet-activating factor (PAF) increases permeability to macromolecules via translocation of eNOS to cytosol and stimulation of eNOS-derived NO signaling cascade. The mechanisms by which NO signaling regulates permeability at adherens junctions are still incompletely understood. Objective We explored the hypothesis that PAF stimulates hyperpermeability via S-nitrosation (SNO) of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 47 publications
(66 reference statements)
1
62
0
Order By: Relevance
“…This notion is supported by our findings that siRNA‐mediated knockdown of Rnd3 expression caused longer time courses of thrombin‐induced barrier dysfunction in HUVEC monolayers in association with extended periods of RhoA activation. It is worth noting that the general concept of signals localized in the perinuclear or centralized areas of the cytoplasm rapidly leading to elevated permeability of the endothelium has previously been shown in studies of endothelial nitric oxide synthase activation localized to the cytosol or Golgi apparatus,72, 73, 74 leading to the downstream S‐nitrosylation of junction‐associated proteins 75…”
Section: Discussionmentioning
confidence: 94%
“…This notion is supported by our findings that siRNA‐mediated knockdown of Rnd3 expression caused longer time courses of thrombin‐induced barrier dysfunction in HUVEC monolayers in association with extended periods of RhoA activation. It is worth noting that the general concept of signals localized in the perinuclear or centralized areas of the cytoplasm rapidly leading to elevated permeability of the endothelium has previously been shown in studies of endothelial nitric oxide synthase activation localized to the cytosol or Golgi apparatus,72, 73, 74 leading to the downstream S‐nitrosylation of junction‐associated proteins 75…”
Section: Discussionmentioning
confidence: 94%
“…12 Recent studies showed that VEGF induced Cui 19 S-nitrosylation of β-catenin, resulting in the dissociation of β-catenin from VE-cadherin and disassembly of AJ complexes. 31,34 In pulmonary EC, PAF and S1P induced S-nitrosylation of β-catenin with disassembly of VE-cadherin and β-catenin at cell-cell contacts, which was augmented by S1pr2 deficiency (Fig 5). Of note, pharmacological blockade of eNOS restored the aggravation of S-nitrosylation of β-catenin and AJ disassembly by S1pr2 deficiency.…”
Section: Discussionmentioning
confidence: 97%
“…22,23,25 Recent studies 31,34 demonstrated that VEGF stimulation of eNOS induced S-nitrosylation of β-catenin, leading to disassembly of AJ complexes. We examined how S1P 2 influenced PAF-induced disassembly of AJ and S-nitrosylation of β-catenin in a monolayer of MLEC.…”
Section: S-nitrosylation Of β-Cateninmentioning
confidence: 99%
“…The regulation of AJ dynamics strongly supports the autocrine role of NO in endothelial cells, separate from the canonical, paracrine role of eNOS in controlling blood flow and hemodynamics. The idea that eNOS-derived NO regulates junctional dynamics is supported by recent results showing that NO posttranslationally nitrosylates b-catenin and p120-catenin promoting its dissociation from VE-cadherin (Marín et al, 2012;Thibeault et al, 2010), and tyrosine nitrates p190RhoGAP (Siddiqui et al, 2011) effects leading to enhanced permeability. Our data showing enhanced TIAM1-VE-cadherin-mediated stabilization of cortical actin explains why mice deficient in eNOS or mice harboring a S1176A allele exhibit reduced vascular leakage in vivo and sheds light on why anti-VEGF therapy reduces vascular permeability but promotes increased blood pressure in patients.…”
Section: Journal Of Cell Sciencementioning
confidence: 94%